Optimization of inner panel thickness for enhanced stiffness and vibration control in car door assemblies - Pandurang Maruti Jadhav; Kishor B. Waghulde; Venushree Khanke; Rupesh V. Bhortake; Prasad D. Kulkarni; Mohammad israr; Muazu Jibrin Musa; Md irfanul Haque Siddiqui; Subhav Singh; Deekshant Varshaney (PLoS ONE, 2025)
The inner panel of the side door acts as a backbone of the door assembly. It is designed to accommodate all the parts required to complete the door assembly and its intended functions. The stiffness of the inner panel indirectly protects the inside passengers from weather conditions and side impacts. The inner panel, outer panel, and a few stiffener plates comprise the door’s structure. The preferred method of hemming is used to connect the inner panel and outer panel at their periphery. In hemming, the crimping of the inner panel is done by using the “U” shape of the outer panel at its periphery. The inner panel and the outer panel together will have a cutout, which will provide clear visibility to both inside passengers and outsiders through this cutout cum window. The closing and opening of this window will be controlled by the electric motor-operated window glass regulator mechanism. The assessment of the Swift Dzire side door assembly was carried out to determine the impact of the inner panel thickness variations on the dynamic characteristics of the door assembly. Effects have been studied and tried out to establish the relationship with thickness. In general, the car users or passengers and the door are in contact. So, the dynamic parameters of the door assembly have been studied, which are related to comfort. These parameters are natural frequencies, mode shapes, dynamic stiffness, and vibrations of the outer panel within the frequency band of 0 Hz to 100 Hz. Mainly, the research study was performed on the baseline inner panel of 1.367 mm thick, and thickness variations were studied between 1.0 mm to 2.4 mm, with an increment of 0.2 mm. The door outer panel/surface dynamic stiffness and vibrations were investigated at 15 critical locations. Based on the output, dynamic results such as modal frequency, mode shape, local dynamic stiffness, and surface vibrations. A relationship has been established between these dynamic parameters and thickness variation of the inner panel, and finally, the optimal thickness has been suggested to meet the required targets.